2006
DOI: 10.1136/ard.2005.048454
|View full text |Cite
|
Sign up to set email alerts
|

Epistatic interaction between FCRL3 and NF B1 genes in Spanish patients with rheumatoid arthritis

Abstract: Background: A Japanese study has described a strong association between rheumatoid arthritis and several polymorphisms located in the Fc receptor-like 3 (FCRL3) gene, a member of a family of genes related to Fc receptors located on chromosome 1q21-23. Objectives: To evaluate the association between rheumatoid arthritis and FCLR3 polymorphisms in a large cohort of Caucasian patients with rheumatoid arthritis and healthy controls of Spanish origin. Owing to the described functional link between the FCRL3 polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 20 publications
0
41
2
Order By: Relevance
“…A meta-analysis suggests an association between NFKB1 to certain autoimmune and inflammatory diseases in the Asian population, but not in the Caucasian population [33]. Likewise, our study found no association of NFKB1 polymorphism with SSc.…”
Section: Discussioncontrasting
confidence: 73%
“…A meta-analysis suggests an association between NFKB1 to certain autoimmune and inflammatory diseases in the Asian population, but not in the Caucasian population [33]. Likewise, our study found no association of NFKB1 polymorphism with SSc.…”
Section: Discussioncontrasting
confidence: 73%
“…Studies of 2 independent North American RA sample sets (3), a large UK sample set (4), and a sample set from New Zealand (5) showed no evidence of association of the SNP with RA (Table 1). A similar finding was obtained in a study of whites of Spanish origin, although, when the authors combined their 2 sample sets and stratified patients and controls by genotype at a putative NFKB1 promoter polymorphism, Ϫ94ins/delATTG, the distribution of FCRL3 Ϫ169T3 C genotypes was significantly different between patients and controls who were heterozygous for the NFKB1 polymorphism (P ϭ 0.001) (6).…”
Section: Meta-analysis Evidence Of a Differential Risk Of The Fcrl3 ؊mentioning
confidence: 52%
“…Studies examining the role of this polymorphism in risk of RA in 9 independent white sample sets, however, have yielded conflicting results (3)(4)(5)(6)(7)(8). Further, a large study of Korean subjects failed to demonstrate association of this single-nucleotide polymorphism (SNP) with RA (9).…”
Section: Meta-analysis Evidence Of a Differential Risk Of The Fcrl3 ؊mentioning
confidence: 99%
“…The association between fcrl3_3 and RA was replicated in an independent Japanese case-control sample collection in a separate study (Ikari et al 2006b), while a large study of Korean subjects failed to demonstrate a significant effect (Choi et al 2006). Several studies have assessed the role of fcrl3_3 in the development of RA in Caucasians, and many failed to replicate the earlier results (Martinez et al 2006a;Eyre et al 2006;Newman et al 2006;Thabet et al 2007). A recent meta-analysis involving more than 10,000 white subjects provided no evidence of association (Begovich et al 2007).…”
Section: Introductionmentioning
confidence: 83%